Beyond the Shannon-Wiener Index: Disparities in Lecturers' Conceptual Knowledge of Effective Species Numbers - Lia Auliandari; Marlina Ummas Genisa (FKIP Universitas Lampung, 2026)
This study aimed to explore lecturers' knowledge of the Shannon-Wiener index and Effective Species Numbers in the context of biodiversity measurement, examining both factual and conceptual knowledge dimensions. A mixed-methods design with an embedded component was employed. Respondents were selected through purposive sampling, and data were collected using an open-ended questionnaire and a procedural competency test (to reinforce qualitative results). The factual knowledge dimension focused on the relevance of species as a measurement unit, while the conceptual knowledge explored index selection, application, and interpretation of the logarithmic base of the Shannon-Wiener index, and emphasis on Effective Species Numbers. The data analysis was carried out through the stages of qualitative and quantitative data analysis, data integration, and conclusion drawing and verification. The results showed that, regarding factual knowledge, lecturers agreed that species remain the basic unit of biodiversity measurement because they reflect ecosystem conditions and serve as a basis for representing environmental health. In the conceptual dimension, the dominant use of the Shannon-Wiener index, based on the natural logarithm, as a methodological standard was found, driven by pragmatic considerations and its suitability with academic textbooks. Lecturers also pointed out the unitless, scaling, and monotonicity properties of the index, as well as the mathematical implications of choosing a logarithmic base. However, absolute differences in logarithmic bases can make index values incomparable across studies. Despite this understanding, a notable gap emerged regarding Effective Species Numbers. While some respondents acknowledged its importance as an advancement that addresses the limitations of entropy-based measures, others were unfamiliar with the concept. This disparity highlighted the need for curricular enhancement and academic updating. Overall, the study underscored the importance of strengthening mathematical-biological literacy and updating ecological education. Beyond routine calculation of traditional biodiversity indices, learning should encourage deeper conceptual reasoning, ecological interpretation, and awareness of contemporary methodological developments. Keywords: shannon-wiener index, effective species numbers, factual knowledge, conceptual knowledge.